2020
DOI: 10.1111/ijpo.12750
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional comparisons of gut microbiome and short‐chain fatty acid levels among children with varied weight classifications

Abstract: Summary Background Limited studies associate changes in microbiota composition and metabolites among children and adolescents with obesity. Decreases in compositional diversity, increases in the proportion of Firmicutes and Bacteroidetes (F/B ratio) and increases in short‐chain fatty acids (SCFAs) have been proposed as contributing factors in the pathophysiology of obesity. Objectives The aim of the current study was to characterize the faecal microbiota composition, diversity, F/B ratio and SCFA levels in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
1
15
0
1
Order By: Relevance
“…The abundance of Verrucomicrobia is relatively low in the human gut microbiota. However, recent research has shown that the abundance of Verrucomicrobia was low in obese children ( 38 , 39 , 60 ), and it has vital benefits. Hence, it is a potential probiotic against metabolic inflammation and obesity ( 61 ).…”
Section: The Relationship Between Pediatric Overweight/obesity and Gu...mentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of Verrucomicrobia is relatively low in the human gut microbiota. However, recent research has shown that the abundance of Verrucomicrobia was low in obese children ( 38 , 39 , 60 ), and it has vital benefits. Hence, it is a potential probiotic against metabolic inflammation and obesity ( 61 ).…”
Section: The Relationship Between Pediatric Overweight/obesity and Gu...mentioning
confidence: 99%
“…The concentration of SCFAs in obese children is low ( 106 ), however, some studies have shown high levels of acetate, propionate, butyrate, and isovalerate in obese children ( 31 , 38 , 99 ), which are positively correlated with BMI z-scores ( 31 ). Despite the potential benefits of SCFAs, the overall function of SCFAs in pediatric overweight/obesity remains unclear.…”
Section: The Relationship Between Pediatric Overweight/obesity and Gu...mentioning
confidence: 99%
“…Therefore, it has become essential to analyze maternal, prenatal, infant, and childhood interactions that could impact infant's health 19 . Childhood obesity is accompanied by shifts in the composition of fecal microbiota with differences between obese and non‐children with obesity (Table 1), 20 which may be accompanied by changes in short‐chain fatty acid levels, potentially associated to the abundance of Proteobacteria 21 or involving fat distribution features in children 22 …”
Section: Introductionmentioning
confidence: 99%
“…18 Therefore, it has become essential to analyze maternal, prenatal, infant, and childhood interactions that could impact infant's health. 19 Childhood obesity is accompanied by shifts in the composition of fecal microbiota with differences between obese and non-children with obesity (Table 1), 20 which may be accompanied by changes in shortchain fatty acid levels, potentially associated to the abundance of Proteobacteria 21 or involving fat distribution features in children. 22 These studies have shown that those children presenting overweight or obesity had a similar microbial profile to each other, being different from the gut microbiota in children with normal-weight as reported in a Chinese pediatric population.…”
mentioning
confidence: 99%
“…However, it remains unclear whether these microbial imbalances were a causal factor in the development of obesity. Moreover, many studies have profiled the gut microbiota of children and adolescents using 16S rRNA gene amplicon sequencing to compare taxonomic composition across weight status [ 41 , 42 , 43 , 44 ], but only a few have explored the associations between markers of insulin resistance and gut microbiome functions [ 36 , 37 , 38 , 45 , 46 ]. None of these studies have used shotgun metagenomics, which is a more robust approach allowing researchers to catalogue all genes present in a sample, identify the taxonomic composition at a species level resolution, and characterize the functional potential of the gut microbiome [ 47 ].…”
Section: Introductionmentioning
confidence: 99%